Rincón de lectura lúdica y creativa como estrategia de enseñanza y aprendizaje en niños y niñas de cuarto grado de educación general básica, en la Unidad Educativa del milenio Ángel Polibio Chaves, cantón San Miguel, periodo 2023-2024 - Montoya Maya, Anthony Joseph (2024)
The present study entitled "Playful and creative reading corner as a teaching and learning strategy in boys and girls in fourth grade of Basic General Education" has as its main objective to strengthen reading through an interactive space that promotes motivation and enjoyment of the reading. The research is carried out at the Millennium Educational Unit “Ángel Polibio Chaves” in San Miguel, Ecuador, and addresses the problem of the shortcomings that exist in reading and deficient skills among students. A reading corner was implemented that allowed students to interact with various texts in a dynamic way, promoting their autonomy and creativity. The instruments used for data collection were interviews with teachers and student observation sheets, which allowed a mixed approach in evaluating the impact of the proposal. The results show a significant improvement in the students' reading fluency and comprehension, as well as an increase in their interest in reading. Implementing this strategy not only contributes to academic performance, but also fosters a positive classroom environment and holistic development of students. It is concluded that the playful and creative reading corner is a fundamental tool to transform the teaching-learning process and promote a reading culture in the current educational context.